â€œBranketâ€ Design as a Safe Deposit Box Security System using Arduino-Based Tap Sensor - Trikusuma, Arsha Raulnadi; Rizqa, Mona; Wardhana, Dhimas Aria; Nada, Noora Qotrun (Universitas PGRI Semarang, 2021)
Safe is a safe place to store valuables or documents. Because they are usually made of strong and hard materials, a safe is a place to store valuables and important documents in the event of a natural disaster or fire. In addition, the safe is also equipped with a locking system so that it can also be used to secure valuables or documents from theft. Usually, safes are used by agencies or companies and the general public who have valuable items or documents. Safe security systems that have been used generally use either a manual lock, a rotary lock, or a digital lock. There are several security system developments in the safe, including using a microcontroller-based password and fingerprint code, a fingerprint sensor and an Arduino UNO-based RF remote control, using a microcontroller via SMS and FSK facilities, and other developments in the safe security system. â€œBranketâ€ (Tap Safe) is a safe with a smart lock system using a knock pattern. The bracket is composed of several electronic components, mainly a microcontroller, a solenoid lock, and a piezoelectric knock sensor. The workflow for using the bracket begins by pressing the power button to turn on the bracket. Then the user sticks his hand into the small space to store or opens the safe by tapping the sensor according to the pattern. Increased security on the bank account includes a locking system with a secret knock pattern, easy to remember by the owner, faster opening of the safe, and the process of opening the safe is difficult for others to know. It is hoped that â€œbranketâ€ will become a new innovation in a unique locking system that still has a high level of security.